The origins and evolution of Islamic law / Wael B. Hallaq. - Hallaq, Wael B., 1955- (Themes in Islamic law ;, 2004)
Long before the rise of Islam in the early seventh century, Arabia had come to form an integral part of the Near East. This book, covering more than three centuries of legal history, presents an important account of how Islam developed its own law while drawing on ancient Near Eastern legal cultures, Arabian customary law and Quranic reforms. The development of the judiciary, legal reasoning and legal authority during the first century is discussed in detail as is the dramatic rise of prophetic authority, the crystallization of legal theory and the formation of the all-important legal schools. Finally the book explores the interplay between law and politics, explaining how the jurists and the ruling elite led a symbiotic existence that - seemingly paradoxically - allowed Islamic law and its application to be uniquely independent of the 'state'.